Annotated record of the detailed examination of Mn deposits from R/V Robert Conrad Cruise 04 stations - Lloyd H Burckle; Roger Hekinian; C Lair; Lamont-Doherty Earth Observatory (PANGAEA, 1963)
The cores described in this report were taken during the R/V Robert Conrad Cruise 04 in March 1963 by the Lamont Geological Observatory, Columbia University. A total of 9 cores were recovered and are available at Lamont-Doherty Earth Observatory for sampling and study.
Supplement to: Burckle, Lloyd H; Hekinian, Roger; Lair, C (1963): Robert Conrad Cruise 04 - Preliminary Megascopic Descriptions of Split Cores. Lamont Geological Observatory, Columbia University, New York, unpublished, 13 pp